2018
DOI: 10.3390/nu10080975
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid and Cognitive Function in Older Individuals

Abstract: Hyperuricemia has been recognized as an independent cardiovascular risk factor in epidemiological studies. However, uric acid can also exert beneficial functions due to its antioxidant properties, which may be particularly relevant in the context of neurodegenerative diseases. In this paper, we critically revise the evidence on the relationship between serum uric acid levels and cognitive function in older individuals, focusing on the etiology of cognitive impairment (Alzheimer’s disease, Parkinson’s dementia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 73 publications
(82 reference statements)
9
82
0
2
Order By: Relevance
“…Despite high heterogeneity in the existing studies, serum uric acid may modulate cognitive function differently according to the etiology of dementia [52]. In this study, hyperhomocysteinemia and hyperuricemia were observed in dementia subtypes with vascular lesions (AD with CVD and vascular dementia).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Despite high heterogeneity in the existing studies, serum uric acid may modulate cognitive function differently according to the etiology of dementia [52]. In this study, hyperhomocysteinemia and hyperuricemia were observed in dementia subtypes with vascular lesions (AD with CVD and vascular dementia).…”
Section: Discussionmentioning
confidence: 72%
“…Current research proves that uric acid can act as a nerve protection against Alzheimer's disease and Parkinson's disease dementia, and hyperuricemia represents a risk factor that indicates the rapid progress of the disease and possible signs of malnutrition [8]. It is known that high uric acid can exert beneficial functions due to its antioxidant properties, which may be particularly relevant in the context of neurodegenerative diseases [52]. However, recent studies have suggested that these two markers are associated with an increased risk of vascular disease [13,53].…”
Section: Discussionmentioning
confidence: 99%
“…Urate, a metabolite of purine nucleotides, is an antioxidant in blood and brain tissue that exerts neuroprotective effects by scavenging reactive oxygen species [ 9 , 10 ]. Although urate has been associated with cognitive function in older people, the data is somewhat conflicting and may depend on the aetiology of the dementia, with protective effects being observed in Parkinson’s dementia and Alzheimer’s disease, but not in vascular dementia [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews and meta-analysis studies focused on the role of uric acid in dementia/cognitive impairment related to senescence, suggesting that uric acid has a protective action in Alzheimer's disease and Parkinson's dementia (hydrophilic antioxidant properties), while hyperuricemia may have a negative influence during vascular dementia (stroke, small vessel cerebrovascular disease) [86,87].…”
Section: Clinical Reportsmentioning
confidence: 99%